2020
DOI: 10.1123/jsm.2019-0222
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-Brand Connection on the Relationship Between Athlete Brand Image and Fan Outcomes

Abstract: This research explored the role of athlete on- and off-field brand image on consumer commitment toward the athlete and associated team, preference by the athlete’s sponsor, and the mediating effect of consumers’ self-brand connection on these relationships. Data were collected from fans of soccer players through a cross-sectional survey promoted on social media platforms. A partial least squares structural equation model examined the direct effects of both athlete brand dimensions on athlete commitment, team c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 91 publications
3
32
0
1
Order By: Relevance
“…promotional campaigns focusing on athletes' commitment to the team, and athlete recruitment policies aligned with team values that go beyond sportrelated characteristics) may contribute to alleviate the uncertainty of team performance and favour spectator overall satisfaction. Furthermore, as core product quality does not depend only on home teams (or strong opponents) and brands within the sport environment affect one another (Kunkel et al, 2020), teams and leagues should work together to develop competitive balance strategies.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…promotional campaigns focusing on athletes' commitment to the team, and athlete recruitment policies aligned with team values that go beyond sportrelated characteristics) may contribute to alleviate the uncertainty of team performance and favour spectator overall satisfaction. Furthermore, as core product quality does not depend only on home teams (or strong opponents) and brands within the sport environment affect one another (Kunkel et al, 2020), teams and leagues should work together to develop competitive balance strategies.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Wu et al (2012) believe that an athlete brand image is a strong stimulus to attract spectators and fans at sports events and to foster intention to purchase products related to athletes. Examining sport brand elements that drive fans’ reactions is paramount to increasing brand health (Biscaia et al , 2016), which suggests the importance of understanding how consumer perceptions about an athlete’s on- and off-field image influence their commitment to support that athlete (Kunkel et al , 2019). Previous studies have suggested that athlete brand image influences attitudinal and behavior outcomes linked with the athlete and related entities such as the athlete’s team and sponsors (Carlson and Donavan, 2013; Williams et al , 2015; Yu, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the influences of athletes’ on- and off-field brand image on fans’ attitudinal and behavioral outcomes require empirical testing. Eventually, there is a lack of empirical evidence demonstrating the impact of athlete associations on fans’ loyalty toward the athlete (Kunkel et al , 2019). Based on the evidence from the literature review, this study seeks to develop and test a theoretical model that hypothesizes the impact of attributes of athlete brand image on fan loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Real Videos." From a branding perspective, TikTok's popularity attests to a shift in consumer culture where authentic brand narratives are valued and self-brand connections are more important than ever (Kunkel, Biscaia, Arai, & Agyemang, 2019). This could explain why Lebron James's inexperienced dance moves became viral content on, and beyond, TikTok.…”
Section: Discussionmentioning
confidence: 99%